2006
DOI: 10.1111/j.1365-2095.2006.00399.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two commercial microdiets on growth and survival of barramundi (Lates calcarifer Bloch) larvae within various early weaning protocols

Abstract: Because of high costs and labour requirements along with the highly variable nutritional value of live feeds, we investigated the possibility of early weaning for barramundi (Lates calcarifer Bloch) larvae aimed at reducing the use of Artemia. Two commercial microdiets, Gemma Micro (Skretting, Australia) and Proton (INVE, Belgium) were compared for growth and survival of larvae using three weaning protocols, until 33 days posthatch (dph). Enriched rotifers were fed to larvae in all protocols through mouth open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 35 publications
2
35
0
1
Order By: Relevance
“…This fact is highlighted by the poor growth and survival observed in shrimp fed on macroalgal biomass only. The positive effect of supplying both live feed and an inert diet has been observed recurrently in larval and juvenile crustaceans (Teshima et al 2000, Thompson et al 2002, Gamboa-Delgado & Le Vay 2009a and fish (Kolkovski et al 1993, Rosenlund et al 1997, Curnow et al 2006.…”
Section: Growth and Survivalmentioning
confidence: 99%
“…This fact is highlighted by the poor growth and survival observed in shrimp fed on macroalgal biomass only. The positive effect of supplying both live feed and an inert diet has been observed recurrently in larval and juvenile crustaceans (Teshima et al 2000, Thompson et al 2002, Gamboa-Delgado & Le Vay 2009a and fish (Kolkovski et al 1993, Rosenlund et al 1997, Curnow et al 2006.…”
Section: Growth and Survivalmentioning
confidence: 99%
“…Further factors that may have increased larval growth and survival when using live feed is that they usually have a much better contrast than artificial feeds and so produce a feeding trigger effect by their continuous movement [24], and that as Artemia actively swim, this ensures a good spatial distribution of food items resulting in more frequent encounters for all larvae [24]. Nevertheless, there have been some successes for larval production from feeding micro-diets after feeding live diets [25]. For example, a range of marine species that were commercial feed two live and dry foods demonstrated excellent larval growth and survival [26] although until now this had not yet been shown in any cyprinidae fish species.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were found for other species (Kolkovski et al, 1997;Rosenlund et al, 1997), when an early co-feeding was attempted. Curnow et al (2006) co-fed Asian sea bass Lates calcarifer on two different inert diets, and verified lower or higher survivals depending on fish size and diet type. It has also been suggested that co-feeding larval sole from 1 mg of larval weight may even improve survival rates at weaning, since it might enhance digestive maturation and/or stimulate digestive secretion (Engrola et al, 2007), even though a higher size dispersion could be observed.…”
Section: Co-feeding Inert Diet From the First-feeding Affects Larval mentioning
confidence: 92%